Violent Institutional Misconduct in the Transition from Juvenile to Adult Correctional Facilities - Trulson, Chad R. (The prison journal, 2022)
This study examines patterns of violent institutional misconduct among a cohort of serious juvenile offenders who were incarcerated in state-level juvenile correctional facilities and then state adult prison institutions. Within the cohort, one group of offenders was immediately transferred to the adult prison system following their incarceration in a juvenile correctional facility. The other portion of the cohort was first released to the community, and then later incarcerated in adult prisons. Results of the analysis indicate that being a younger prison inmate with a history of childhood trauma and considered a high-rate violent institutional misconduct perpetrator as a juvenile ward were significant predictors of engaging in violent misconduct in adult prisons. Implications for theory, research, and practice are discussed.